Development of Scrapbook-Based Visual Learning Media Using the Picture and Picture Model to Enhance Elementary Students’ Poetry Writing Skills - Yuni Nur Cahyani; Nugraheti Sismulyasih SB (Jurnal Paedagogy, 2026)
This study aims to develop scrapbook-based learning media grounded in the Picture and Picture model and to determine its feasibility and effectiveness in improving fourth-grade students’ poetry writing skills. The study employed a Research and Development (R&D) approach based on Sugiyono’s model, which includes stages such as problem identification, product design, expert validation, field testing, revision, and implementation. Data were collected through test instruments (pretest and posttest) and non-test techniques, including observations, interviews, and questionnaires. Data analysis involved normality testing, paired-samples t-tests, and normalized gain (N-gain) analysis. The feasibility results indicate that the product was rated highly feasible, with scores of 95% from media experts and 88% from material experts, yielding an average of 91.5%. The t-test results (p < 0.05) demonstrate a statistically significant improvement in students’ poetry writing skills following the intervention. Furthermore, the N-gain scores were 0.5617 (small-scale trial) and 0.720 (large-scale trial), both categorized as moderate. These findings suggest that scrapbook-based media integrated with the Picture and Picture model is both feasible and effective in enhancing students’ poetry writing skills. The integration of visual instructional models with tactile, multimodal media such as scrapbooks helps bridge the gap between abstract ideas and written expression. This study offers practical implications for educators in fostering creative literacy through structured visual stimuli.